2020
DOI: 10.1073/pnas.1912984117
|View full text |Cite
|
Sign up to set email alerts
|

K6-linked SUMOylation of BAF regulates nuclear integrity and DNA replication in mammalian cells

Abstract: Barrier-to-autointegration factor (BAF) is a highly conserved protein in metazoans that has multiple functions during the cell cycle. We found that BAF is SUMOylated at K6, and that this modification is essential for its nuclear localization and function, including nuclear integrity maintenance and DNA replication. K6-linked SUMOylation of BAF promotes binding and interaction with lamin A/C to regulate nuclear integrity. K6-linked SUMOylation of BAF also supports BAF binding to DNA and proliferating cell nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…6 D and E). These results are consistent with previous findings to indicate that cGAS is active in the cytoplasm whereas nuclear cGAS is inactive (Kujirai et al, 2020;Michalski et al, 2020;Zhao et al, 2020). The accumulation levels of sfGFP-DARPin-LA6 and Halo-BAF at the rupture sites were lower in cells with nuclear cGAS-sfCherry compared to those with the cytoplasmic cGAS-sfCherry (Fig.…”
Section: Cytoplasmic Cgas Accumulates At the Rupture Sites And Affects Lc And Baf Accumulationsupporting
confidence: 93%
“…6 D and E). These results are consistent with previous findings to indicate that cGAS is active in the cytoplasm whereas nuclear cGAS is inactive (Kujirai et al, 2020;Michalski et al, 2020;Zhao et al, 2020). The accumulation levels of sfGFP-DARPin-LA6 and Halo-BAF at the rupture sites were lower in cells with nuclear cGAS-sfCherry compared to those with the cytoplasmic cGAS-sfCherry (Fig.…”
Section: Cytoplasmic Cgas Accumulates At the Rupture Sites And Affects Lc And Baf Accumulationsupporting
confidence: 93%
“…It has been reported that LA and/or LC play a role in retaining BAF inside the nucleus ( Lin et al, 2020 ). Therefore, we examined if BAF localization is affected by depletion of specific lamins by staining endogenous BAF in WT, Lmna -KO, Lmnb1 -KO and Lmnb2 -KO MEFs using two different antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies on SENP3, we discovered a number of SUMOylation-regulated proteins that function in interphase cells (Han et al, 2010;Huang et al, 2009;Lao et al, 2018;Liu et al, 2020;Ren et al, 2014;Wang et al, 2016;Zhou et al, 2016). More recently, we also found that the SUMOylation-deSUMOylation cycle regulates the functions of barrier-to-autointegration factor (BAF) in nuclear integrity maintenance and DNA replication in mammalian cells (Lin et al, 2020). Here, as an extension of our previous work, we found that SENP3 and SENP5 impact mitotic progression via deSUMOylating AurA and spatiotemporally controlling its kinase activity for precise spindle assembly and maintenance of genomic stability.…”
Section: Introductionmentioning
confidence: 97%